The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1088/0004-637x/769/1/50
|View full text |Cite
|
Sign up to set email alerts
|

On the Internal Dynamics of Starless Cores: Stability of Starless Cores With Internal Motions and Collapse Dynamics

Abstract: In order to understand the collapse dynamics of observed low-mass starless cores, we revise the conventional stability condition of hydrostatic Bonnor-Ebert spheres to take internal motions into account. Because observed starless cores resemble Bonnor-Ebert density structures, the stability and dynamics of the starless cores are frequently analyzed by comparing to the conventional stability condition of a hydrostatic Bonnor-Ebert sphere. However, starless cores are not hydrostatic but have observed internal mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
(78 reference statements)
1
10
0
Order By: Relevance
“…It was mentioned in Section 1 that the infall velocities for the cores L1689B and L694-2 were observed to be faster than expected, see Lee et al (2007). A theoretical model proposed by Seo et al (2013), in which the collapse of the cores was modeled by means of a uniform density or as Bonner-Ebert spheres, demonstrated that these cores may have infall velocities up to -1.0 or -1.5 times the velocity normalized with the speed of sound, which indicates an enhanced collapse. Meanwhile, for the cores L1544 and L63, in which the collapse appeared to be normal, the magnitude of the infall velocity was around -0.5 times the speed of sound 4 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It was mentioned in Section 1 that the infall velocities for the cores L1689B and L694-2 were observed to be faster than expected, see Lee et al (2007). A theoretical model proposed by Seo et al (2013), in which the collapse of the cores was modeled by means of a uniform density or as Bonner-Ebert spheres, demonstrated that these cores may have infall velocities up to -1.0 or -1.5 times the velocity normalized with the speed of sound, which indicates an enhanced collapse. Meanwhile, for the cores L1544 and L63, in which the collapse appeared to be normal, the magnitude of the infall velocity was around -0.5 times the speed of sound 4 .…”
Section: Discussionmentioning
confidence: 81%
“…The magnitudes of the infall velocities reported here have been taken from fig.6ofSeo et al (2013).Copyright line will be provided by the publisher…”
mentioning
confidence: 99%
“…Redman et al 2002;Crapsi et al 2005;Bacmann et al 2016;Kim et al 2020), internal structure and dynamics (e.g. Lee et al 1999Lee et al , 2001Redman et al 2004;Seo et al 2013;Roy et al 2014) due to its relative isolation and simple morphology.…”
Section: The L1689 Molecular Cloudmentioning
confidence: 99%
“…L1689B is a candidate gravitationally bound prestellar core. Its stability and age remain uncertain, with a number of studies identifying the core as contracting or showing signs of infall (Redman et al 2004;Sohn et al 2007;Lee & Myers 2011;Seo et al 2013), while Schnee et al (2013) found it to be static. Redman et al (2002) found L1689B to be relatively long-lived, with an age of at least one freefall time inferred from CO freezeout in the core's center; however, Lee et al (2003) argued that the core is chemically young, with a lack of freezeout of HCO+ and also a potential lack of CO freezeout.…”
Section: L1689bmentioning
confidence: 99%
See 1 more Smart Citation